A rhodium/silicon co-electrocatalyst design concept to surpass platinum hydrogen evolution activity at high overpotentials - Lili Zhu (Nature Portfolio, 2016)
Design of hydrogen evolution catalysts needs to balance the hydrogen adsorption energy to facilitate easy adsorption and desorption. Here, the authors report a composite catalyst where hydrogen adsorption occurs on rhodium and desorbs from silicon which has a lower adsorption energy.